2014
DOI: 10.1136/amiajnl-2013-002579
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes regarding privacy of genomic information in personalized cancer therapy

Abstract: Patients generally expressed low levels of concern regarding privacy of genomic data, and many expressed willingness to consent to sharing their genomic data with researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…This was a cross-sectional survey with conventional sampling. These questions were part of a larger questionnaire and focused on demographics, definitions, expectations and knowledge about research [24, 25]. The knowledge questionnaire included 16 questions each of which could be answered “True”, “False” or “Do not know” (Supplementary Document 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was a cross-sectional survey with conventional sampling. These questions were part of a larger questionnaire and focused on demographics, definitions, expectations and knowledge about research [24, 25]. The knowledge questionnaire included 16 questions each of which could be answered “True”, “False” or “Do not know” (Supplementary Document 1).…”
Section: Methodsmentioning
confidence: 99%
“…The information-seeking questionnaire contained multiple-choice questions that assessed where participants looked for information and how they used the information that they found. Additional questions assessed attitudes regarding privacy of genomic information and research participation [24, 25]. We recorded participants’ age, insurance, and clinical variables such as duration of illness, cancer stage, history of cancer therapy, history of genetic testing, and consent for tissue banking from the participants’ medical records.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence regarding public awareness of confidentiality risks is conflicting (Kaufman et al, 2009;Brothers et al, 2011;Oliver et al, 2011;Trinidad et al, 2012;Rogith et al, 2014). A survey study (N = 1041) about consent to a hypothetical biobank found that 75% of participants disapproved of using their genetic material because of security concerns (Kerath et al, 2013).…”
mentioning
confidence: 99%